Increasing Students' Learning Outcomes IPA Class IV SDN 12 Mundam Sakti Using Images - Saryenti, Evi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
Improving the quality of education cannot be separated from teaching aids as teaching media, one of which is image media. Here the image media can be used to improve students' mastery of the material. The purpose of this study was to determine the application of image media in science learning to improve students' mastery of the material and analyze the impact on the use of image media. The subjects of this study were the fourth grade students of SDN 12 Mundam Sakti, totaling 25 students. This study uses an instrument of observation and test results. The application of image media can attract students' attention in identifying the Animal Life Cycle, this can be seen from the increased activity and collaboration of students in discussions. The maximum application of image media can increase student mastery, while the average student learning outcomes in the first cycle of 66.4 increase to 83.6 in the second cycle and the classical mastery target is achieved by 70%. From these results it can be concluded that using image media can improve learning outcomes of fourth graders at SDN Mundam Sakti in 2019/2020.